The Civil Disobedience Against Unjust Laws in Thai Society: A Case Study of the Supreme Court Judgment No. 7008/2014 - Sripetsuphan, Panya; Sripetsuphan, Kanchanarat (Journal of Law and Political Affairs, 2025)
This research aims to analyze civil disobedience against unjust laws in Thai society: A case study of the Supreme Court judgment no. 7008/2014 as an important acts of civil disobedience. The researcher used a documentary research method by synthesizing the actions that are important acts of civil disobedience according to John Rawls’s view from the expressions, limitations, and conditions of civil disobedience through content analysis from documents and interpretation of judgments according to the specified conceptual framework. The research results found that (1) the civil disobedience against the law in the case of the Supreme Court’s decision no. 7008/2014 was consistent with the important acts of civil disobedience, consists of (1.1) violation of a law, and intended to be so; (1.2) nonviolent; (1.3) accompanied by willingness to accept the legal consequences; (1.4) addressed to the majority’s sense of justice; (1.5) addressed to a sense of justice that is mainly incorporated in the law and social institutions. And (2) the civil disobedience against the law in the case of the Supreme Court’s decision no. 7008/2014 was not consistent with the important acts of civil disobedience, consists of (2.1) public and with unfair notice given and (2.2) usually performed to bring about a not change in the law or in policies of the government. Therefore, those who intend to engage in civil disobedience should be aware that once they have done so, they must accept the consequences of violating the law that may be criminally punished. They should also engage in civil disobedience in other cases at the same time so that civil disobedience can result in changes to unjust laws in Thai society to be amended.